EPC Agenda 2005-03-24 - Academic Senate:::::::::
Educational Policies Committee. Provost Report. Agenda approved. Minutes of 10/8/15 – Approved. Chair Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Draft policy/resolution on the Use of Release Time. Classroom renovations task force – long term implications. WASC update. Resolution regarding SSU Campus Based Equity Program, Second Round approved for the Senate agenda. Rohnert Park Mayor visit – topics and questions. Classroom Renovation committee report. EPC Report. FSAC Report. SAC Report. Associated Students Report. CFA Report. Senate agenda approved.